ANALISIS REAKSI PASAR SAHAM SYARIAH TERHADAP DAMPAK CORONA VIRUS DISEASE (COVID-19) OUTBREAK DI INDONESIA - Ahmad Muhaimin; Yunida Een Friyanti; Fatimah Yunus (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
This study intends to examine how the Islamic stock market responds to the impact of the Corona virus with the example of 10 Islamic stock issuers contained in the Jakarta Islamic Index (JII) by separating the estimates into three periods. The first period is in December 2019-March 2020, which is the period for the emergence of the corona virus but has not been officially reported in Indonesia. The next period is April-July 2020 when the pandemic has officially entered Indonesia and the Large Scope Social Restrictions (PSBB) have been implemented, and the third time span is August-December 2020 when the Implementation of Restrictions on Community Activities (PPKM) is enforced. This study will examine how the response from daily returns from 10 JII issuers. In addition, this study uses a descriptive quantitative method with the research method used is purposive sampling. Where this research provides the findings that after the announcement of the Coronavirus pandemic in December 2019 it had an impact throughout the world and made the Islamic stock market experience negative developments. During the PSBB and PPKM periods, several sectors experienced positive developments, this is quite good progress, especially for investors who have received certainty regarding the spread of the Corona virus in Indonesia so that preventive measures can be taken. In times of a pandemic like this, the average stock price tends to decline, one of which is because investors have sold their shares for fear that the shares will decrease in value in the future, but this is not the same as Islamic finance which emphasizes that they are more stable than ordinary shares which have been proven. on the shares of JII and its 10 issuers.